Audiovisual integration of simple stimuli: spatial congruency effects unaffected by working memory load - Chen, Jingxin; Li, Qingqing; Tao, Hanlin; Xu, Chenfei; Gao, Yulin; Yang, Jingjing; Wu, Qiong (Frontiers in Psychology, 2025)
The present study sought to investigate whether working memory (WM) load influences the spatial congruency effect in audiovisual (AV) integration using simple stimuli. Participants completed an AV localization task under three WM load conditions (0-back, 1-back, 2-back), Spatially congruent AV stimuli consistently facilitated responses regardless of working memory (WM) load. Statistical analyses found no significant interactions between WM load and audiovisual integration for reaction time (RT), accuracy, sensitivity (d’), or auditory enhancement effects (p < 0.05). Critically, Bayesian analysis in the present study provided strong evidence against the existence of such an interaction (BF ≈ 0.0001), although independent replication is warranted to confirm this finding. These findings indicate that spatially congruent AV integration is robust across different levels of working memory load, suggesting that it occurs at a low-level perceptual stage and is automatic.